SPOROZOAN INFECTION IN PENAEUS SEMISULCATUS AT MANDAPAM - Thomas, M M (Indian Journal of Fisheries, 2011)
A few specimens of Penaeus semisulcatus collected from Mandapam areawere found infected with a microsporidian parasite tentatively identified as Thelohaniaduorara Iversen and Manning whicli has 'been earlier reported only fromthe. U.S.A. Although these parasites resemble T. duorara' closely, they differsignificantly from the American specimens in the shape of the spores, and pansporoblasts.